Molecular characterization of prosomeric and intraprosomeric subdivisions of the embryonic zebrafish diencephalon. Issue 5 (29th January 2013) - Lauter, Gilbert; Söll, Iris; Hauptmann, Giselbert
Abstract During development of the early neural tube, positional information provided by signaling gradients is translated into a grid of transverse and longitudinal transcription factor expression domains. Transcription factor specification codes defining distinct histogenetic domains within this grid are evolutionarily conserved across vertebrates and may reflect an underlying common vertebrate bauplan. When compared to the rich body of comparative gene expression studies of tetrapods, there is considerably less comparative data available for teleost fish. We used sensitive multicolor fluorescent in situ hybridization to generate a detailed map of regulatory gene expression domains in the embryonic zebrafish diencephalon. The high resolution of this technique allowed us to resolve abutting and overlapping gene expression of different transcripts. We found that the relative topography of gene expression patterns in zebrafish was highly similar to those of orthologous genes in tetrapods and consistent with a three‐prosomere organization of the alar and basal diencephalon. Our analysis further demonstrated a conservation of intraprosomeric subdivisions within prosomeres 1, 2, and 3 (p1, p2, and p3). A tripartition of zebrafish p1 was identified reminiscent of precommissural (PcP), juxtacommissural (JcP), and commissural (CoP) pretectal domains of tetrapods. The constructed detailed diencephalic transcription factor gene expression map further identified molecularly distinct thalamic and prethalamic rostral and caudal domains and a prethalamic eminence histogenetic domain in zebrafish. Our comparative gene expression analysis conformed with the idea of a common bauplan for the diencephalon of anamniote and amniote vertebrates from fish to mammals. J. Comp. Neurol. 521:1093–1118, 2013. © 2012 Wiley Periodicals, Inc.